Liquid‐Cell Electron Microscopy: Observation of Undamped 3D Brownian Motion of Nanoparticles Using Liquid‐Cell Scanning Transmission Electron Microscopy (Part. Part. Syst. Charact. 6/2020). (9th June 2020) - Welling, Tom A. J.; Sadighikia, Sina; Watanabe, Kanako; Grau‐Carbonell, Albert; Bransen, Maarten; Nagao, Daisuke; van Blaaderen, Alfons; van Huis, Marijn A.
Abstract : In article number 2000003, Alfons van Blaaderen, Marijn A. van Huis, and co‐workers image mobile nanoparticles in solution using a dedicated liquid cell holder inside a transmission electron microscope. The observation of the diffusion of single nanoparticles in real time without influence of the electron beam enables future in‐situ studies of nanoparticle interactions and self‐assembly processes.